Comparative Analysis of Highly Sensitive PCF for Chemical Sensing in THz Regime - Islam, Mohammad Saiful; Sadath, Anwar; Islam, Md. Rakibul; Faisal, Mohammad (Photonics Letters of Poland, 2020)
Nowadays photonic crystal fiber (PCF) is used for sensing purposes in different fields. In this work, we have proposed a PCF based chemical (Benzene and Ethanol) sensor. Finite Element Method (FEM) based software COMSOL 5.3a is used to investigate the numerical characteristics for the proposed structure. From the numerical analysis, we obtained high sensitivity with low losses for an optimum core diameter of 210 µm. Our proposed PCF works on a broad range of core diameters and THz frequency spectra. The fabrication of this model is very simple due to its simplistic design structure. Full Text: PDF References Md.F.H. Arif, Md.J.H. Biddut, "A new structure of photonic crystal fiber with high sensitivity, high nonlinearity, high birefringence and low confinement loss for liquid analyte sensing applications", Sensing Bio-Sensing Res. 12, 8 (2017). CrossRef P. Kumar, Md.H. Bikash, K. Ahmed, S. Sen, "A Novel Hexahedron Photonic Crystal Fiber in Terahertz Propagation: Design and Analysis", Photonics 6(1), 32 (2019). CrossRef S. Asaduzzaman, K. Ahmed, T. Bhuiyan, T. Farah, "Hybrid photonic crystal fiber in chemical sensing", SpringerPlus 5, 748 (2016). CrossRef Md.S. Islam, J. Sultana, J. Atai, D. Abbott, S. Rana, M.R. Islam, "Ultra low-loss hybrid core porous fiber for broadband applications", App. Opt. 56(4), 1232 (2017). CrossRef S. Atakaramians, S. Afshar, H. Ebendorff-Heidepriem, M. Nagel, B.M. Fischer, D. Abbott, T.M. Monro, "THz porous fibers: design, fabrication and experimental characterization", Opt. Expr. 17(16), 14053 (2009). CrossRef